Studying Diversity, Migration and Urban Multiculture Convivial Tools for Research and Practice - Berg, Mette Louise; Nowicka, Magdalena (UCL Press, 2019)
Anti-migrant populism is on the rise across Europe, and diversity and multiculturalism are increasingly presented as threats to social cohesion. Yet diversity is also a mundane social reality in urban neighbourhoods. With this in mind, Studying Diversity, Migration and Urban Multiculture explores how we can live together with and in difference. What is needed for conviviality to emerge and what role can research play? This volume demonstrates how collaboration between scholars, civil society and practitioners can help to answer these questions.